Wages, Profits, and Capital Intensity: Evidence from Matched Worker‐Firm Data - Arai, Mahmood (Journal of Labor Economics, 2003)
Swedish data on workers matched with firms’ balance‐sheet reports are used to examine the relation between wages and firms’ ability to pay. Results indicate that experienced and highly educated workers are sorted into profitable firms. Wages are positively correlated with profits and the capital‐labor ratio, after controlling for worker quality, degree of effort supervision, job characteristics, local unemployment, firms’ employment history, and employer size. Lester’s “range of pay” due to rent sharing is around 12%–24% of the mean wage in Sweden, which is close to the estimates for the United States and United Kingdom.